Multifunctional nanozyme for multimodal imaging-guided enhanced sonodynamic therapy by regulating the tumor microenvironment. Issue 33 (23rd July 2021) - Liu, Shuling; Zhang, Wei; Chen, Qiaoqi; Hou, Jingxin; Wang, Junrui; Zhong, Yixin; Wang, Xingyue; Jiang, Weixi; Ran, Haitao; Guo, Dajing
Abstract : Sonodynamic therapy (SDT) is a highly promising approach for cancer therapy, but its efficacy is severely hampered by the low specificity of sonosensitizers and the unfavorable characteristics of the tumor microenvironment (TME). Abstract : Sonodynamic therapy (SDT) is a highly promising approach for cancer therapy, but its efficacy is severely hampered by the low specificity of sonosensitizers and the unfavorable characteristics of the tumor microenvironment (TME), such as hypoxia and glutathione (GSH) overexpression. To solve these problems, in this work, we encapsulated IR780 and MnO2 in PLGA and linked Angiopep-2 (Ang) to synthesize a multifunctional nanozyme (Ang-IR780-MnO2 -PLGA, AIMP) to enhance SDT. With Ang functionalization to facilitate blood–brain barrier (BBB) penetration and glioma targeting, and through the function of IR780, these nanoparticles (NPs) showed improved targeting of cancer cells, especially mitochondria, and spread deep into tumor centers. Upon low-intensity focused ultrasound (LIFU) irradiation, reactive oxygen species (ROS) were produced and induced tumor cell apoptosis. Combined with the specific mitochondria-targeting ability of IR780, the sonodynamic effects were amplified because mitochondria are sensitive to ROS. In addition, MnO2 exhibited enzyme-like activity, reacting with the high levels of hydrogen protons (H + ), H2 O2 and GSH in the TME to continuously produce oxygen and consume GSH, which further enhanced the effect of SDT. Moreover, Mn 2+ can be released in response to TME stimulation and used as a magnetic resonance (MR) contrast agent. In addition, IR780 has photoacoustic (PA)/fluorescence (FL) imaging capabilities. Our results demonstrated that AIMP NPs subjected to LIFU triggering maximally enhanced the therapeutic effect of SDT by multiple mechanisms, including multiple targeting, deep penetration, oxygen supply in situ and GSH depletion, thereby significantly inhibiting tumor growth and distal metastasis without systemic toxicity. In summary, this multifunctional nanozyme provides a promising strategy for cancer diagnosis and treatment under the intelligent guidance of multimodal imaging (PA/FL/MR) and may be a safe clinical translational method.